2011
DOI: 10.1084/jem.20102057
|View full text |Cite
|
Sign up to set email alerts
|

Muc5ac: a critical component mediating the rejection of enteric nematodes

Abstract: The mucin Muc5ac is essential for the expulsion of Trichuris muris and other gut-dwelling nematodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
299
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(308 citation statements)
references
References 30 publications
8
299
0
1
Order By: Relevance
“…Perhaps surprisingly, ablation of Muc2 in vivo only led to a delayed T. muris expulsion during acute infection, even though a Th2‐mediated immune response prevailed 73. Further studies showed there was an induction of the polymeric mucin Muc5ac, normally a gastric and lung mucin, which was important for T. muris parasite expulsion and suggested a protective function for this mucin in the intestine 9. This was confirmed using Muc5ac‐deficient mice, which were completely susceptible to T. muris infection unlike their wild‐type counterparts.…”
Section: Gi Nematode Infection and Mucinsmentioning
confidence: 83%
See 3 more Smart Citations
“…Perhaps surprisingly, ablation of Muc2 in vivo only led to a delayed T. muris expulsion during acute infection, even though a Th2‐mediated immune response prevailed 73. Further studies showed there was an induction of the polymeric mucin Muc5ac, normally a gastric and lung mucin, which was important for T. muris parasite expulsion and suggested a protective function for this mucin in the intestine 9. This was confirmed using Muc5ac‐deficient mice, which were completely susceptible to T. muris infection unlike their wild‐type counterparts.…”
Section: Gi Nematode Infection and Mucinsmentioning
confidence: 83%
“…Importantly, the susceptible phenotype was not reversed even after administration of anti‐IFN‐γ to skew the Th1 dominated environment generated in chronic infection towards a Th2‐directed immune response, normally associated with resistance 10. Importantly, there was an induction of Muc5ac transcripts in T. suis infected pigs, suggesting a protective role across species,74 and there is data to suggest that Muc5ac may also have a broad antihelminth action as Muc5ac null mice were also impaired in their ability to efficiently expel N. brasiliensis and T. spiralis 9…”
Section: Gi Nematode Infection and Mucinsmentioning
confidence: 98%
See 2 more Smart Citations
“…171 Consistent with these data, Muc5ac is only upregulated in resistant mouse strains 170 and Muc5ac-deficient mice have impaired expulsion of T. muris, N. brasiliensis, and T. spiralis. 173 Increased mucus production and the mucin switch are largely driven by IL-13, 173 IL-4, 174 and IL-22, 175 but the principle of physical obstruction provided by mucus layers can also be extended to other mucosal sites such as the lungs where the lectin surfactant protein-D, which acts as a lubricant, is needed for optimal protection against the pulmonary stage of N. brasiliensis infection. 176 Another expulsion mechanism is the release of various proteins by activated granulocytes and epithelial cells, most of which are toxic to parasites.…”
Section: Expulsionmentioning
confidence: 99%